A study to compare the outcomes of laser myringotomy and conventional incision myringotomy - Pudukulangara, Shruthi; Megalamani, Somanath B.; Gadag, Ravindra P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to compare the outcomes of laser myringotomy and incision myringotomy in terms of operating time, patency of opening, hearing improvement, and disease recurrence. Methods: This study is a prospective study done among 35 children and 68 ears. All cases which were diagnosed to have otitis media with effusion were randomly assigned into two groups: group 1 was treated with diode laser myringotomy and group 2 was treated with conventional incision myringotomy without grommet insertion. These patients were followed up at regular intervals and compared in terms of operating time, patency of opening, recurrence of disease and hearing improvement. Results: Diode laser myringotomy took an average operating time of 6.38 minutes and the patency of opening was maintained for an average of 13.59 days, compared to the average operating time for incision myringotomy of 9 minutes, and the patency of opening being 12.35 days. These differences were statistically significant (p<0.0001 for operating time and p=0.041 for patency of opening). Hearing improvement was also found to be better in laser myringotomy group (p=0.021). Conclusions: Diode laser myringotomy is an effective, easy and less time-consuming modality than incision myringotomy for the treatment of otitis media with effusion.